Influência do boro no teor, acúmulo e eficiência nutricional em porta-enxertos de caramboleira - Xavier, Clariana Valadares [UNESP]; Natale, William (Revista Brasileira de Ciencias Agrarias, 2017)
The ability to absorb, transport and use nutrients is different between plants. There are few studies in the literature about the influence of boron (B) on the nutritional efficiency in rootstocks of the star fruit. In view of the lack of information, the objective of this study was to evaluate the influence of B on the content, accumulation, efficiency of absorption, transport and nutrient use in rootstocks of the star fruit. The design was randomized blocks, with five doses of B: zero; 1; 2; 3; 4 mg dm-3 of B and four replicates. At 170 days after application of B, the plants were harvested, separated in aerial part and roots, dried, weighed, ground and determined the contents, calculated the accumulations, the efficiency of absorption, transportation and use of macro and micronutrients. The calcium (Ca) and B contents in the roots of the rootstocks decreased with increasing doses of B. The results showed that higher doses of boron increased the transport efficiency and Ca utilization.
Influence of boron on the content, accumulation and nutritional efficiency in rootstock of star fruit
Keywords: Absorption of Nutrients; Averrhoa carambola L.; Macronutrients